2000
DOI: 10.1074/jbc.m002095200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Alzheimer's β-Secretase Protein BACE

Abstract: The cerebral deposition of amyloid ␤-peptide is an early and critical feature of Alzheimer's disease. Amyloid ␤-peptide is released from the amyloid precursor protein by the sequential action of two proteases, ␤-secretase and ␥-secretase, and these proteases are prime targets for therapeutic intervention. We have recently cloned a novel aspartic protease, BACE, with all the known properties of ␤-secretase. Here we demonstrate that BACE is an N-glycosylated integral membrane protein that undergoes constitutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
101
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 13 publications
7
101
0
Order By: Relevance
“…2A) and sulfation rate analyses. While this article was in preparation, we became aware of two reports (43,44) on the biosynthesis of BACE that reported some observations similar to ours. In the report by Capell et al (44) regarding the prosegment removal of human BACE, their data, like ours, revealed that this processing occurs in the TGN and that BACE S traffics more rapidly than BACE F toward the TGN.…”
Section: Discussionmentioning
confidence: 89%
“…2A) and sulfation rate analyses. While this article was in preparation, we became aware of two reports (43,44) on the biosynthesis of BACE that reported some observations similar to ours. In the report by Capell et al (44) regarding the prosegment removal of human BACE, their data, like ours, revealed that this processing occurs in the TGN and that BACE S traffics more rapidly than BACE F toward the TGN.…”
Section: Discussionmentioning
confidence: 89%
“…It has been previously shown by immunofluorescence microscopy that ectopically expressed BACE is localized primarily in the TGN and the endosomal system (9,24,25). However, significant quantities of the glycoprotein are also present in the endoplasmic reticulum, at the cell surface (9,26,27), and to a lesser extent in the lysosomes (9,24). Ectopically expressed BACE demonstrated a highly punctuate staining pattern reminiscent of vesicular compartments in H4-B cells (Fig.…”
Section: Treatment With Lysosomal Inhibitors Cause Accumulation Of Bamentioning
confidence: 99%
“…BACE appears to localize to the Golgi apparatus (5). Despite about 40% amino acid similarity between BACE and pepsin proteases (9), the cysteine residues in BACE involved in intramolecular disulfide bonds are not conserved with other pepsin family members (10). Such fundamental structural differences may explain why ␤-secretase is insensitive to pepstatin, a specific inhibitor of pepsin proteases (7).…”
mentioning
confidence: 94%